Islamisation of microfinance: a case study of Maldives - Hassan, Rusni (American-Eurasian Network for Scientific Information (AENSI), Jordan, 2011)
Maldives is a hundred per cent Muslim country that lies in the heart of the Indian Ocean. It has a unique geography consisted on 1,190 islands forming 26 natural atolls spreading over 900 square kilometer. The population of the country is just around 300,000. Maldives is ranked 100 out of 178 countries on the Human Development Index, and is classified as a country with medium human development. The biggest economic challenge in Maldives is to distribute the income evenly to all parts of the nation. It is, thus, difficult to develop all the inhabited Islands scattered across the archipelago due to lack of transportation facilities. The capital of Maldives, Male’ is the only island that has been developed in terms of health, ducation and infrastructure. The rest of the nation is still developing at a slow pace. Microfinance is the only type of development tool to the Island population. The nation is alien to Islamic finance until early this year. Though Islamic banking is introduced in the country, the benefit of the bank is only enjoyed by the people in the capital. The rest of the population is left with bare minimum or without any type of modern banking facility. Hence, the only source of development capital is the capricious periodic disbursements for target areas by foreign aid agencies in collaboration with the government. The problem with the microfinance facility in Maldives is that it is based on the conventional structure. The objective of this paper is to suggest ways to Islamize microfinance in Maldives and to shed light on the benefits that the Maldivians could enjoy by using Islamic microfinance. In the course of doing this, the paper explores the potential sources to raise capital for microfinancing in Maldives. It is anticipated that the outcome of this paper would also supplement efforts by other geographically dispersed lowlying island nations.